Demystifying Foreign Direct Investment dynamics in emerging economies: An ISM–MICMAC analysis - Paul Grover, Srabani; Chotia, Varun; Datta, Satyaki; Shetty, Sham Ranjan (Economics and Business Review, 2026)
Foreign Direct Investment (FDI) has emerged as a pivotal force in the economic development trajectory of emerging economies, catalysing growth, technological transfer, and global integration. The World Investment Report of 2024 states that, as of 2023, 65.1% (867.4 billion) of all global FDI inflow went to emerging economies, up from just 16.4% (222.7 billion) in 2000. The existing literature on FDI determinants mostly used the multiple regression approach. We undertake a novel approach using Interpretive Structural Modelling (ISM) coupled with MICMAC analysis. This qualitative methodology provides a holistic understanding of the hierarchical relationships and interdependencies among FDI drivers. A key finding of this study is that the three most significant factors influencing FDI in emerging economies are political stability, corruption, and the state of infrastructure. These factors significantly impact all other drivers in the system. The drivers were categorised into clusters using MICMAC based on their dependence and driving power.